Human profile and apostolic deed of Francis Xavier - Lamet, SJ, Pedro Miguel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Every third day of his life he spent navigating the sea. He accomplished an extraordinary human deed in his time. In his way of proceeding and by the conditions of the time period, he sketched the first dialogue between East and West. He remained in union with the Society that he helped to found along with Ignatius, which he called the Society of Love. But his strength facing the powers of the world was the irruption of gratuity and trust in the total support of God – in the midst of a self-serving world. His example still stands for today, as he lived in a time very similar to ours: one of discoveries and great change, also of corruption and economic ambition.
Keywords: Francis Xavier; Jesuits; Society of Jesus; missions; enculturation; religious dialogue